Examining Economic Crime Policy: Evidence from Indonesia - Emiliya Febriyani; Topo Santoso (Journal of Judicial Review, 2022)
The development of global economic activity has given birth to various types of new crimes in the economic field. To tackle crime in the economic field, Indonesia has Emergency Law No. 7 of 1955. However, the existence of Emergency Law No. 7 of 1955 is considered to have been unable to tackle crime in the existing economic field. In addition, there are currently many laws, outside Emergency Law No. 7 of 1955, regulating crime prevention in the economic field. This study aims to review and examine the existing economic crime policies in Indonesia. This research is normative juridical research with the library research method. The library materials used consist of primary, secondary, and tertiary legal materials. The information was then analyzed qualitatively and descriptively. The regulation of economic crime in Indonesia has been regulated narrowly and broadly. In a narrow sense, economic crimes are all actions listed in the TPE Act.